Let ‘No’ be ‘No’: When Librarians say ‘No’ to Instruction Opportunities - Anna White (In the Library with the Lead Pipe, 2023)
In Brief: This paper presents a review of the literature on when, why, and how librarians say ‘no’, drawing from work on vocational awe, service orientation and deference behavior, and criticism of the one-shot model. Findings from a survey describing the experiences of approximately 285 American and Canadian academic librarians with instruction responsibilities to examine impact of personal and professional demographics, burnout, pedagogical concerns.